Effect of drip-fertigation levels on gobhi sarson (Brassica napus) performance under Punjab conditions - SHARMA, RAJNI; KUMAR, DIVYA S; BRAR, A S (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted to study the effect of drip irrigation and fertigation levels on performance of gobhi sarson (Brassica napus L.) during rabi 2016-18. The results revealed that application of irrigation through drip at 100% of CPE (I1.0) recorded highest values for growth components, viz. periodic plant height, dry matter accumulation and leaf area index than I0.8 (80% of CPE) and I0.6 (60% of CPE). Maximum seed and oil yield were recorded at I1.0, which was statistically at par with I0.8 but significantly higher than I0.6 and absolute control. Utilization of water-soluble fertilizers through drip at 100% RDF (F1.0) recorded highest growth components along with seed and oil yield than that produced by 80 and 60% RDF (F0.8 and F0.6). Among treatment combinations, drip-fertigation at I1.0 or I0.8 with F1.0 or F0.8 significantly enhanced seed and oil yield of gobhi sarson than absolute control (flood irrigation and manual application of RDF).